Políticas públicas para formação de professores – um resgate na história da educação - Silva, Maria Vanda Silvino da (2018)
This work rescues in the context of Brazilian education, to the historical and political reconstruction of the teacher, identifying his professional action and social valorization. In order to make a scrutiny of his role as educator under the hegemony of power. The general objective is to portray the political context of the models of the teaching profession, through the description of historical facts and phenomena, seeking to identify in the history of Brazilian education the political condition of the teacher facing the interests of the policies of the government systems that have impacted the formation and acting. the methodology consists of a bibliographical and documentary research. As to the proposed method, the work comprises a description of the political and historical process of the model of the teaching profession in four contexts: the first in colonial Brazil, in which the remote aspects of the teacher profession, from Egypt under the aegis of the absolute power of the pharaoh, until the moment when the professor happens to be of the dominion of the church; the second characterizes the teacher in the model of colonial and imperial domination and brings an approach to conflicts of political, religious and monarchical interests in the delineation of the teaching profession; in the third political model of the teacher under republican rule and the conflicts between the state and society; and the fourth political model of teacher in the democratic state under US influence in the field of public policy. And lastly, the analysis of the data, being observed the teacher, as protagonist, subordinated to the power control organs hegemonically and historically constituted. Revealed that its professional action, attends the ideological conceptions of State, whereby it is formed and carries on its activities, without political autonomy, being subordinated to a formation that lacks the critical development of its own professional identity.